Optical characterization of conductive metal oxide thin films - Pan, Ruoping (2014)
Thickness dependent and growth temperature dependent ZnO thin film optical properties (complex dielectric function, band gap energy and exciton binding energy) have been studied by using spectroscopic ellipsometry (SE) based on Yoshikawa and Adachi’s model. Comparing with bulk ZnO material, ZnO thin film exhibits an expansion in the band gap energy and exciton binding energy as physical dimension scale down due to quantum confinement effect and bond-order-length-strength correlation, which significantly suppress the dielectric constants. The blue shift in dielectric constants originates from the band gap expansion and electron-photon coupling. In addition, the band gap energy and exciton binding energy of ZnO thin film reduced with increasing growth temperature, as a consequence of bond contraction and electron-photon interaction, which enhances the dielectric constants as well results in blue shift of absorption edge.